2011
DOI: 10.1039/c1gc15266a
|View full text |Cite
|
Sign up to set email alerts
|

Solvents derived from glycerol modify classical regioselectivity in the enzymatic synthesis of disaccharides with Biolacta β-galactosidase

Abstract: Green solvents made from glycerol change the classical regioselectivity of Biolacta N o 5 -galactosidase, from (1→4) toward (1→6) linkages when 2M concentration was used. In order to explain these results, the non-proteic compounds present in Biolacta preparation were separated by precipitation with 10 ammonium sulfate and the remaining protein extract was used to set reactions with appropriate organic solvents to find that the regioselectivity towards the β(1 6) isomer is retained. According to proteomic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 52 publications
(69 reference statements)
0
25
0
Order By: Relevance
“…Thus, fluorinated glycerol derivatives, such as the closely related 1,3-bis(2,2,2trifluoroethoxy)propan-2-ol [3F.0.3F], have been successfully used as reaction media in epoxidation and enzymatic reactions. 38,[47][48][49]…”
Section: Scope Of the Synthesis With Different Bases And Alcoholsmentioning
confidence: 99%
“…Thus, fluorinated glycerol derivatives, such as the closely related 1,3-bis(2,2,2trifluoroethoxy)propan-2-ol [3F.0.3F], have been successfully used as reaction media in epoxidation and enzymatic reactions. 38,[47][48][49]…”
Section: Scope Of the Synthesis With Different Bases And Alcoholsmentioning
confidence: 99%
“…Recently, it has been shown that the use of green solvents, 20,21 such as biomass derived solvents or ionic liquids, as co-solvents in the enzymatic reaction lead to a variation of the enzyme activity. [22][23][24][25][26][27][28][29] Biomass derived solvents show some new and attractive advantages, as there are made from a renewable source, they are (presumably) less toxic, exhibit low volatility, and possess tuneable physicochemical properties. 20,21,[30][31][32] We have previously described the use of some of these biomass derived solvents in the transglycosylation reaction catalyzed by Biolacta b-galactosidase, using p-nitrophenyl-b-D-galactopyranoside (p-NP-b-Gal) as donor and GlcNAc as acceptor, changing the regioselectivity of the enzyme from a mixture of b(1A4) and b(1A6) towards the synthesis of only b(1A6) oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions (500 mL) contained 10 U mL À1 -standard b-fructofuranosidase activity, 200 g L À1 sucrose in 0.2 M sodium acetate buffer pH 5.5, and 30% (v/v) nal concentration of solvents, except for GCL and DMA at 2 M. 28,55,56 Spain). Data obtained aer 65 min total analysis time were processed by Borwin soware (v. 1.5; Jasco Inc.).…”
Section: Enzyme-catalyzed Transfructosylating Reactions With Solventsmentioning
confidence: 99%